ANALISIS PORTOFOLIO INVESTASI PADA SAHAM SEKTOR PROPERTI YANG TERDAFTAR DI JAKARTA ISLAMIC INDEX DENGAN PENDEKATAN SHARPE INDEX, TREYNOR INDEX, DAN JENSEN INDEX - Muhammad Saufa Yardha (Studia Economica : Jurnal Ekonomi Islam, 2015)
This study aimed to analyze the investment portfolio in the property sector stocks listed in JII using the Sharpe Index, Treynor Index and Jensen Index. Research carried out by using a different test is based on data about the performance of the portfolio during the period of 2010-2014. Based on the data processing obtained F value Calculate for the return of the portfolio in a row that the BSDE amounted to 23 904, CTRA amounted to 21,250, LPKR amounted to 44 981, and SMRA amounted to 38 729, then to see the F Calculate there, the conclusion that F count> F table is on BSDE 23 904> 3.885294, at CTRA 21,250> 3.885294, on LPKR amounted to 44 981> 3.885294, and the SMRA 38 729> 3.885294, and a significance level of <0.05 then the conclusion is not the differences significant return between BSDE, CTRA, LPKR, and SMRA approach Sharpe Index, Treynor Index and Jensen Index. While in terms of performance, there are differences in the performance of the portfolio using Sharpe Index, Treynor Index and Jensen Index.